PENGARUH INTERAKSI ANTARA TOTAL QUALITY MANAGEMENT DENGAN SISTEM PENGHARGAAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA MANAJERIAL (Studi Empiris pada SMK Di Kabupaten Karanganyar) - Muhammad Agung Prabowo, Endang Mardiyati dan (Paradigma, 2015)
This emperical research conducted 2014, is intended to test the hyphothesis about the influences variables of TQM, interaction between TQM with reward system, and interaction between TQM with organizational commitmentÂ to managerial performance at the level of SMK in Karanganyar.The research design is survey and quantitative approach. Respondents were teachers and employees in the SMK of public and private school in Karanganyar, who held managerial positions amounted to 142 pearsons from 33 schools. It uses the regression with the absolute residual test method to test hypothesis.The results of this research showed that the proposed third hypothesis can be accepted, meaning that TQM (X1), interaction between TQM with reward system (X2) and interaction between TQM with organizational commitment (X3) have positive and significant effect on managerial performance.Â Keywords : Â TQM, reward system, organizational commitment, managerial performance